2014
DOI: 10.17221/50/2013-pps
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of spinosad on some biochemical and biological parameters of Glyphodes pyloalis Walker (Lepidoptera: Pyralidae)

Abstract: Piri F., Sahragard A., Ghadamyari M. (2014): Sublethal effects of spinosad on some biochemical and biological parameters of Glyphodes pyloalis Walker (Lepidoptera: Pyralidae). Plant Protect. Sci., 50: 135-144.The susceptibility of G. pyloalis larvae to spinosad was studied using the leaf dip method. Treatment with doses of spinosad sublethal concentrations (LC 10 , LC 20 , LC 30 , LC 40 of 0.026, 0.045, 0.065, 0.090 ppm, respectively) was applied. A significant difference in the effects was observed between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
4
15
0
1
Order By: Relevance
“…The decline in the level of glycogen is probably due to its breakdown in the fat bodies and its release in the haemolymph as trehalose under stress conditions (Nath 2003). Our results are in agreement with the results of Piri et al (2014), who showed that spinosad significantly decreased the glycogen content of the fifth larval instar of Glyphodes pyloalis (Walker).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The decline in the level of glycogen is probably due to its breakdown in the fat bodies and its release in the haemolymph as trehalose under stress conditions (Nath 2003). Our results are in agreement with the results of Piri et al (2014), who showed that spinosad significantly decreased the glycogen content of the fifth larval instar of Glyphodes pyloalis (Walker).…”
Section: Discussionsupporting
confidence: 93%
“…Hussain et al (2009) reported an insignificant effect of spinosad at LC 10 and LC 20 concentrations on the esterase activity of susceptible strains of T. castaneum. Piri et al (2014) showed no significant differences in the activities of α-and β-esterases in Glyphodes pyloalis larvae treated with LC 20 , LC 30 , and LC 40 concentrations of spinosad and the control. However, S. littoralis larvae treated with indoxacarb showed a significant increase in α and β-esterase activities (Gamil et al 2011).…”
Section: Discussionmentioning
confidence: 79%
“…Based on our result and results of the studies conducted by Vuković et al (2014) the good candidates for mixtures could be chlorpyriphos or cypermethrin. Piri et al (2014) proved that the exposure of females of the lesser mulberry pyralid to sublethal doses of spinosad may reduce the female fecundity. The reduction of female fertility in the multicoloured Asian lady beetle was reported by Galvan et al (2005).…”
Section: Discussionmentioning
confidence: 99%
“…Fox, et al, reported that the reproductive capacity of adult female insects is affected largely by their body protein content [19]. Piri, et al, noted that proteins are important for individual-level fitness-associated traits such as body size, growth rate and fecundity [20]. At high levels of organization, proteins have been linked to population dynamics, life cycles and even biological diversification [20].…”
Section: Introductionmentioning
confidence: 99%
“…Piri, et al, noted that proteins are important for individual-level fitness-associated traits such as body size, growth rate and fecundity [20]. At high levels of organization, proteins have been linked to population dynamics, life cycles and even biological diversification [20]. Some of the biochemical composition of Acanthoscenlides obtectus Say, S. oryzae, S. granarius and T. confusum have been investigated [17][18][19]21,22].…”
Section: Introductionmentioning
confidence: 99%